Development and optimization of fast dissolving oro-dispersible films of granisetron HCl using Box-Behnken statistical design - Hema Chaudhary; Samita Gauri; Permender Rathee; Vikash Kumar (Faculty of Pharmacy, Cairo University, 2013)
The aim was to develop and optimize fast dissolving oro-dispersible films of granisetron hydrochloride (GH) by two-factor, three-level Box-Behnken design as the two independent variables such as X1 (polymer) and X2 (plasticizer) were selected on the basis of the preliminary studies carried out before the experimental design is being implemented. A second-order polynomial equation to construct contour plots for the prediction of responses of the dependent variables such as drug release (Y1), Disintegration time (Y2), and Y3 (Tensile strength) was studied. The Response surface plots were drawn, statistical validity of the polynomials was established to find the compositions of optimized formulation which was evaluated using the Franz-type diffusion cell. The designs establish the role of the derived polynomial equation and contour plots in predicting the values of dependent variables for the preparation and optimization.